A fair share for the orphans: ethical guidelines for a fair distribution of resources within the bounds of the 10-year-old European Orphan Drug Regulation. Issue 3 (24th September 2011) - Pinxten, Wim; Denier, Yvonne; Dooms, Marc; Cassiman, Jean-Jacques; Dierickx, Kris
Abstract : For a significant number of patients, there exists no, or only little, interest in developing a treatment for their disease or condition. Especially with regard to rare diseases, the lack of commercial interest in drug development is a burning issue. Several interventions have been made in the regulatory field in order to address the commercial disinterest in these conditions. However, existing regulations mainly focus on the provision of incentives to the sponsors of clinical trials of orphan drugs, and leave unanswered the overarching question about the rightful place of orphan drugs in resource allocation systems. In this article, we analyse the ethical aspects of funding research and development in the field of rare diseases. We then propose an ethical framework that can help health policy makers move forward in the difficult matter of fairly allocating resources for the prevention, diagnosis and treatment of rare diseases.